Screening for Lactobacillus plantarum Strains That Possess Organophosphorus Pesticide-Degrading Activity and Metabolomic Analysis of Phorate Degradation - Li, Changkun; Ma, Yuzhu; Mi, Zhihui; Huo, Rui; Zhou, Tingting; Hai, Huricha; Kwok, Lai-yu; Sun, Zhihong; Chen, Yongfu; Zhang, Heping (Frontiers in Microbiology, 2018)
This work performed a large scale assessment for organophosphorus pesticides (OPPs) degradation activity of 121 Lactobacillus (L.) plantarum strains. Six L. plantarum strains (P9, IMAU80110, IMAU40100, IMAU10585, IMAU10209, and IMAU80070) were found to possess high capacity of degrading three commonly used OPPs, namely dimethoate, phorate, and omethoate; and they were selected for more detailed characterization. Moreover, the three organophosphorus pesticides were mainly detected in the culture supernatants but not in the cell extracts, further confirming that the OPPs were degraded rather than absorbed by the cells. Among the six selected strains, P9 was most tolerant to gastrointestinal juices and bile. We thus used ultra-high performance liquid chromatography electron spray ionization coupled with time-of-flight mass spectrometry (UPLC/ESI-Q-TOF/MS) to generate the metabolomic profiles of the strain P9 growing in MRS medium with and without containing phorate. By using orthogonal partial least squares discriminant analysis, we identified some potential phorate-derived degradative products. This work has identified novel lactic acid bacteria resources for application in pesticide degradation. Our results also shed light on the phorate degradation mechanism by L. plantarum P9.